Social Criticism in Barbara Schöneberger's Song - Hapitta, Okky Dwi (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
Three of Barbara Schöneberger's songs from the album Jetzt singt sie auch noch...! criticize women in society. This study aims to elucidate German perceptions about women. In this study, a descriptive qualitative technique was used as the research methodology. The research's data consists of phrases and words taken from the lyrics of three songs by BarbaraSchöneberger from the album Jetzt singt sie auch noch…! Document analysis techniques, note-taking, and listening wereused to collect data. We then employed careful observation and listening to analyze the data. This study used the LiterarySociology approach, which draws on Alan Swingewood's concept of Literary Sociology. The results of the study show that: (1) From Barbara Schöneberger's album Jetzt singt sie noch...!, the first three tracks Three categories can be used to categorize the stereotypes about women: (a) those that focus on how they appear physically; (b) those that highlight how they are perceived as capable; and (c) those that depict women as nothing more than objects for other women's bodies. (2)Examined social issues include the following: Social criticism can be divided into three categories: (a) criticism of morality in society, which breeds stereotypes and discrimination against women; (b) criticism of economics, which focuses on unethical economic growth that fuels social unrest; and (c) criticism of gender, which addresses women's roles as objects of all women and gender norms that restrict women to household duties.